Comprehensive Study on Hydrogen Production for Sustainable Transportation Planning: Strategic, Techno-Economic, and Environmental Impacts - Mohammadamin Ganji; Mohammad Gheibi; Alireza Aldaghi; Klodian Dhoska; Sonila Vito; Sina Atari; Reza Moezzi (Hydrogen, 2025)
Hydrogen energy is essential in the transition to sustainable transportation planning, providing a clean and efficient alternative to traditional fossil fuels. As a versatile energy carrier, hydrogen facilitates the decarbonization of diverse transportation modes, including passenger vehicles, heavy-duty trucks, trains, and maritime vessels. To justify and clarify the role of hydrogen energy in sustainable transportation planning, this study conducts a comprehensive techno-economic and environmental assessment of hydrogen production in the USA, Europe, and China. Utilizing the Shlaer–Mellor method for policy modeling, the analysis highlights regional differences and offers actionable insights to inform strategic decisions and policy frameworks for advancing hydrogen adoption. Hydrogen production potential was assessed from solar and biomass resources, with results showing that solar-based hydrogen production is significantly more efficient, producing 704 tons/yr/km2, compared to 5.7 tons/yr/km2 from biomass. A Monte Carlo simulation was conducted to project emissions and market share for hydrogen and gasoline vehicles from 2024 to 2050. The results indicate that hydrogen vehicles could achieve near-zero emissions and capture approximately 30% of the market by 2050, while gasoline vehicles will decline to a 60% market share with higher emissions. Furthermore, hydrogen production using solar energy in the USA yields a per capita output of 330,513 kg/yr, compared to 6079 kg/yr from biomass. The study concludes that hydrogen, particularly from renewable sources, holds significant potential for reducing greenhouse gas emissions, with policy frameworks in the USA, Europe, and China focused on addressing energy dependence, air pollution, and technological development in the transportation sector.